Public Space as a Hybrid Space in the Urban Sprawl Phenomenon - Darmansjah Tjahja Prakasa; Ibrahim Tohar (Journal of Architectural Design and Urbanism, 2026)
Urban sprawl is commonly examined as inefficient physical expansion from city centers to suburban area. This pattern-oriented view often overlooks the long-term socio-spatial processes through which suburban public spaces adapt, negotiate, and become hybrid. The gap of urban sprawl studies has been dominated by spatial map analysis and the short-term causes and impacts of the phenomenon. The novelty in this study focuses on the integration of five aspects of Stan's hybrid space: coexistence, transfusion, interconnection, ambivalence, and heterogeneity as a long-term, strengthened by Carr et al.'s approach as public-space quality dimensions responsive, democratic, meaningful, and accessible space. A qualitative case study approach was employed through purposive sampling involving five participants, consisting of community leaders, community-organization members, housing-estate representatives, the developer, and the Sub-District government. Supported by in-depth interviews, field observations, and visual documentation. The findings show that public spaces in Darmo Permai operate as hybrid spaces with different levels of interaction between housing-estate residents and kampung residents. Punden Barongan Watu is the most dominant hybrid space, while the cemetery area, Sub-District Office, and Residential Park show specific but stronger interaction patterns. This study contributes to urban sprawl and public space studies by positioning public space quality as an indicator of socio-spatial resilience and negotiated coexistence in suburban transformation.